Monte-Carlo simulation of three dimensional ion dynamics in polymers - Wagner, Achim; Kliem, Herbert (MRS online proceedings library, 2011)
Dynamic Monte-Carlo simulations of three dimensional ion motions are carried out based on a multi-well potential model. A parallel plate capacitor is modeled with an ionic conducting polymer having two ideal blocking electrodes. Positive ions (maximum 1000) are located on a cubic lattice with a maximum size of 100×100×100 locations. A negative background charge, constant in space and time, is used to provide charge neutrality. The positive ions can perform hops between neighboring sites with a probability corresponding to distributed energy barriers. To calculate the potentials due to an interaction of the ions the method of images is used. The steady state and the dynamic properties are studied after application of a voltage step in dependence on the sample thickness, the ion concentration and the voltage. A simulation of a space charge polarization yields an explanation for the experiments in the time and in the frequency domain.